Effect of ethanol on the longevity and abscission of bougainvillea flower - Hossain, A.B.M.S.; Boyce, A.N.; Majid, H.M.A.; Chandran, S.; Zuliana, R. (2007)
The experiment was carried out to study the effect of different concentrations of ethanol on bougainvillea flower vase life and delayed abscission. Young and fresh flowers were harvested from 4-year-old bougainvillea trees randomly. Flower stems (petiole) were placed individually in an open solution containing different concentrations of ethanol immediately after harvesting. The solutions used for treatment were water (control), 2, 4, 8, 10, 20, 30, 40, 50 and 70 ethanol. Positive responses were found in the case of 8 and 10 ethanol after 5 days of treatment. Flower longevity was 2 days longer in 8 and 10 ethanol than in water control and other concentrations of ethanol. Petal wilting and abscission occurred 2 days later than water control. Perianth abscission was later in 8 and 10 ethanol than water control. Percent petal scar (color changing) was later in water control, 2, 4, 8 and 10 than 20, 30, 40, 50 and 70 ethanol The result showed that the flower vase life was significantly affected by ethanol concentrations and longevity was more in 8 and 10 ethanol than water control and other concentrations.